Vertical transfer and functional characterization of cotton seed core microbiome - Wu, Chongdie; Zhang, Xin; Fan, Yongbin; Ye, Jingyi; Dong, Lingjun; Wang, YuXiang; Ren, YinZheng; Yong, HongHong; Liu, Ruina; Wang, Aiying (Frontiers in Microbiology, 2024)
Microbiome within plant tissues is pivotal for co-evolution with host plants. This microbiome can colonize the plant, with potential transmission via seeds between parents and offspring, affecting seedling growth and host plant adaptability to the environment. We employed 16S rRNA gene amplicon analysis to investigate the vertical distribution of core microbiome in cotton seeds across ecological niches (rhizosphere, root, stem, leaf, seed and seed-P (parental seed)) of the three cotton genotypes. The findings demonstrated a significant decrease in microbiome diversity and network complexity from roots, stems, and leaves to seeds. The microenvironment exerted a more substantial influence on the microbiome structure of cotton than the genotypes. The core endophytic microorganisms in cotton seeds comprised 29 amplicon sequence variants (ASVs) affiliated with Acidimicrobiia, Alphaproteobacteria, Bacilli, Bacteroidia, Clostridia, Gammaproteobacteria, and unclassified_Proteobacteria. These vertically transmitted taxa are widely distributed in cotton plants.Through 16S rRNA gene-based function prediction analysis of the cotton microbiome, we preliminarily understood that there are potential differences in metabolic capabilities and phenotypic traits among microbiomes in different microhabitats. In conclusion, this study demonstrated the crucial role of the microenvironment in influencing the cotton microbiome and offered insights into the structures and functions of the cotton seed microbiome, facilitating future crop yield enhancement through core seed microbiome regulation.